(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The smelting behavior of direct reduction iron powder containing Ni and Cu from co-reduction followed by a magnetic separation of copper slag and nickel laterite was investigated in this paper. The results show that the perfect ternary alloy with 90.66% Fe, 5.24% Ni, 1.20% Cu and minor impurities can be prepared by smelting under optimum conditions at 1550 °C for 30 min with 1.1 slag basicity. The corresponding recoveries of Fe, Ni, and Cu were 92.77%, 96.27% and 96.24%, respectively. In addition, basicity has a significant effect on slag fluidity. The optimum basicity of slag is approximately 1.1, which is beneficial for both metal recovery and desulfuration. Compared with the direct reduction iron powder, the Fe-Ni-Cu ternary alloy contains a higher metal content and less sulfur from the smelting process and is a superior material for producing weathering steel. Hence, it is very feasible to use an electric arc furnace to smelt direct reduction iron powder to produce a high quality Fe-Ni-Cu ternary alloy.